SUBSTANTIATION OF THE MODEL OF THE PROCESS OF FORMATION OF CIVIC ACTIVITY OF STUDENTS IN THE EDUCATIONAL WORK OF THE UNIVERSITIES - Khabibulla Muratov Abdukodirovich (Journals Park Publishing, 2022)
The solution to the problem of the formation of civic activity of students, in our opinion, is possible due to the creation of the most favorable conditions, which are reflected in the model of formation of civic activity of students in the educational work of the university in the modern process of the formation of civil society in Uzbekistan. To construct a model means to define and describe the content of activities to achieve a designated goal within a certain subject of education (a certain institution), as well as to determine the sequence of its implementation [46, p. 142]. Thus, we proceed from the fact that the formation of a civic-active personality involves the creation of a complex model that unites the process of the entire system of organizing the educational work of a university, including certain goals, tasks, stages, levels, optimal means, directions and forms of work that predicts the most significant changes in the personality of the student [70].
Keywords: model; pedagogy; university